Recombinant human klotho protects against hydrogen peroxide-mediated injury in human retinal pigment epithelial cells via the PI3K/Akt-Nrf2/HO-1 signaling pathway. Issue 5 (2nd May 2022) - Wen, Xuewei; Li, Song; Zhang, Yanfei; Zhu, Liang; Xi, Xiaoting; Zhang, Shuyuan; Li, Yan
ABSTRACT: Globally, age-related macular degeneration (AMD) is a common irreversible ophthalmopathy. Oxidative stress of retinal pigment epithelial cells is involved in AMD occurrence and development. Klotho is an anti-aging protein with antioxidant properties. We investigated the protective properties of Klotho on hydrogen peroxide (H2 O2 )-induced injury of retinal pigment epithelial cells (ARPE-19 cells) and its associated pathomechanisms. We found that Klotho pretreatment for 24 h could up-regulate Bcl-2 levels, decrease the cleaved-caspase-3 and Bax levels, inhibit H2 O2 -induced ARPE-19 cell apoptosis, and promote cell proliferation. Klotho pretreatment inhibited the H2 O2 -mediated elevations of reactive oxygen species (ROS) in ARPE-19 cells. It enhanced antioxidant activities of the cells and restored the glutathione peroxidase (GPX), superoxide dismutase (SOD2), catalase (CAT), as well as malondialdehyde (MDA) levels to close to the normal level. N-acetylcysteine (NAC), a reactive oxygen scavenger, could reverse the harmful effects of H2 O2 on proliferation, apoptosis, and oxidative stress of ARPE-19 cells. Further, Klotho pretreatment enhanced Akt phosphorylation and expression as well as nuclear translocation of Nrf2 in H2 O2 -treated ARPE-19 cells. This indicates that Klotho protects cells from oxidative stress by activating phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt)-nuclear factor E2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) signaling pathway. Klotho is, therefore, a potential preventive or treatment option for AMD. Graphical Abstract: uf0001